2008
DOI: 10.1165/rcmb.2007-0226oc
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Induce an Early Steroid Resistance in Airway Smooth Muscle Cells

Abstract: We have previously shown that long-term treatment of airway smooth muscle (ASM) cells with a combination of TNF-a and IFN-g impaired steroid anti-inflammatory action through the up-regulation of glucocorticoid receptor beta isoform (GRb) (Mol Pharmacol 2006;69:588-596). We here found that steroid actions could also be suppressed by short-term exposure of ASM cells to TNF-a and IFN-g (6 h) as shown by the abrogated glucocorticoid responsive element (GRE)-dependent gene transcription; surprisingly, neither GRa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 56 publications
(71 reference statements)
9
90
0
1
Order By: Relevance
“…2B). In keeping with data published previously (28,39,40), TNF␣ and IFN␥, when used in combination, induced additional steroid insensitivity, with the highest concentration of fluticasone (10 Ϫ6 M) inhibiting CXCL10 release by 19.2 Ϯ 3.4% (from 17,070.7 Ϯ 4642.9 pg/ml to 14,095 Ϯ 4428.2 pg/ml; Fig. 2C).…”
Section: Tnf␣-and Ifn␥-induced Cxcl10supporting
confidence: 91%
“…2B). In keeping with data published previously (28,39,40), TNF␣ and IFN␥, when used in combination, induced additional steroid insensitivity, with the highest concentration of fluticasone (10 Ϫ6 M) inhibiting CXCL10 release by 19.2 Ϯ 3.4% (from 17,070.7 Ϯ 4642.9 pg/ml to 14,095 Ϯ 4428.2 pg/ml; Fig. 2C).…”
Section: Tnf␣-and Ifn␥-induced Cxcl10supporting
confidence: 91%
“…The expression of these GC-insensitive proasthmatic proteins by ASM correlated with the severity of asthma. We and others replicated this finding in vitro using cultured human ASM cells (ASMCs) exposed to a combination of TNF-a and IFN-g (8)(9)(10). We showed that the induction of a variety of proasthmatic genes, namely CD38, CXCL10, CX3CL1, and CCL5, by TNF-a and IFN-g was surprisingly insensitive to the inhibition by GC (9,11).…”
mentioning
confidence: 61%
“…We showed that the induction of a variety of proasthmatic genes, namely CD38, CXCL10, CX3CL1, and CCL5, by TNF-a and IFN-g was surprisingly insensitive to the inhibition by GC (9,11). This "corticosteroidinsensitive" state induced by TNF-a and IFN-g was associated with a marked suppression of GC receptor (GR)-mediated transactivation activities (8)(9)(10). These findings showing that the responsiveness of ASMCs to GC therapy could be dramatically affected by proasthmatic cytokines led us to suggest that the reduced sensitivity of "airway structural" cells to GC during inflammatory condition may contribute to the overall CSI seen in patients with severe asthma.…”
mentioning
confidence: 99%
“…TNF α -другой важный воспалительный цитокин, регулирующий экспрес сию CD38 в дыхательных путях. Патофизиологичес кую роль TNF α доказывает наличие его в высоких концентрациях в бронхоальвеолярной жидкости и мокроте пациентов с астмой [43]. TNF α -важный фактор в изменении сопротивления дыхательных путей и формировании обструкции при БА [20,44].…”
Section: обзорыunclassified